STRATEGI PENGEMBANGAN AGROINDUSTRI BERBAHAN BAKU BUAH SEGAR (STUDI KASUS SOP BUAH ICA DI MANADO) - Yosiko Hizkia Panambunan; Agnes E. Loho; Eyverson ., Ruauw (AGRI-SOSIOEKONOMI, 2016)
This study aims to identify the external factors and internal factors that can affect the agro-industry â€œSop Buah Icaâ€, and formulate strategies in the development of agro-industry Sop Buah Ica in the study area.The research was done on location â€œSop Buah Icaâ€ in Manado Boulevard, during the three months from May 2015 through July 2015. The data obtained are primary and secondary data. Primary data sourced from opinions and interviews with relevant parties, among others, business owners, customer and employees who are the subject of research. Secondary data is data obtained by researchers who comes from a document from the relevant authorities, such as Internet and library resources or literature books. Data were analyzed using SWOT analysis.Based on the results of SWOT analysis diagram; Sop Buah ICA business is located in quadrant I, which is an aggressive strategy. In this position, a situation which is very beneficial for business Sop Buah has a bright prospect in the future because it has the power and the enormous opportunities that should be utilized. So that needs to be done some of strategies that need to be done, which is to harness capital is always available with the purchase of business purposes in fruit soup, take advantage of market opportunities with the selling price, Fruit Sop product promotion in public places to add new customers, take advantage of other fruits that are on the market, for the purposes of processing Sop Buah, it can also be helpful as it gives a new color to the contents of the fruit Sop, look for other suppliers.